2019
DOI: 10.2174/1568009619666190718141647
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Soluble Programmed Death Ligand 1 as a Prognostic Factor in Hepatocellular Carcinoma in Egyptian Patients

Abstract: Background: The expression of programmed cell death ligands on tumor cells has a role in the suppression of antitumor immunity, resulting in tumor immune evasion. Objective: In this study, we evaluated the prognostic value of the soluble form of programmed death-ligand1 (sPD-L1) in Egyptian hepatocellular carcinoma (HCC) patients. Methods: This prospective cohort study was performed between November 2016 to November 2018 on 85 individuals (25 HCC patients, 25 HCC with vascular invasion and/or extrahepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…A recent systematic review identified 544 articles (16.2%) published in PubMed about HCC in Egypt [106]. In Egypt, some abnormalities in molecular pathways involved in HCC have been identified [107,108] but other abnormalities need to be identified on a large scale of HCC Egyptian patients using advanced technology. Identification of molecular characteristics of HCC Egyptian patients will pave the way for personalized therapy toward improvement of their overall survival [107].…”
Section: Hcc Researchmentioning
confidence: 99%
“…A recent systematic review identified 544 articles (16.2%) published in PubMed about HCC in Egypt [106]. In Egypt, some abnormalities in molecular pathways involved in HCC have been identified [107,108] but other abnormalities need to be identified on a large scale of HCC Egyptian patients using advanced technology. Identification of molecular characteristics of HCC Egyptian patients will pave the way for personalized therapy toward improvement of their overall survival [107].…”
Section: Hcc Researchmentioning
confidence: 99%
“…In most cases, the level of circulating sPD-L1 was found to be enhanced in the plasma of patients with the indicated pathology compared to healthy control (see Table 1 . For the oncology indications, the presence of sPD-L1 and its significance are discussed in the following studies: AEC [ 41 ]; BTC [ 42 , 43 ]; brain tumors [ 26 , 44 ]; CRCC [ 45 , 46 ]; CRC [ 47 ]; cutaneous melanoma [ 48 ]; DLBCL [ 49 , 50 ]; EOC [ 51 , 52 ]; ENKTL [ 53 , 54 ]; HNSCC [ 36 ]; HCC [ 55 , 56 , 57 ]; HL [ 54 , 58 ]; mesothelioma [ 59 , 60 ]; NC [ 61 , 62 ]; PGC [ 63 , 64 , 65 ]; NSCLC [ 66 , 67 ]; PC [ 68 ]; PCNSL [ 50 ]; STS [ 69 , 70 ]; TC [ 71 ]; TNBC [ 72 ]; WM [ 73 ].…”
Section: The Pd-1/pd-l1 Checkpointmentioning
confidence: 99%
“…[ 27 ] Other prognostic factor, the soluble form of programmed death ligand 1 (sPD-L1) on tumor cells, when elevated, has also been found to be prognostic indicator for poor outcome. [ 28 ] Huge HCC, defined as a tumor diameter greater or equal to 10 cm, complete resection was believed to be potentially curative; however, the approach and extent of resection remain unclear. HCC with diaphragmatic invasion often requires tumor en bloc with part of the diaphragm is often resected and anterior approach is recommended in minimizing intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%